Genome-scale CRISPR Cas9a knockout screen reveals genes that control glioblastoma susceptibility to the alkylating agent temozolomide. Issue 1 (31st December 2022) - Awah, Chidiebere U.; Winter, Jan; Ogunwobi, Olorunseun O.
ABSTRACT: Glioblastoma is the most fatal of all primary human brain tumors, with a 14-month median survival. The mainstay therapy for this tumor involves temozolomide, surgery, radiotherapy, and tumor-treating electric field. Cancer resistance to commonly available chemotherapeutics remains a major challenge in glioblastoma patients receiving treatment and unfavorably impacts their overall survival and outcome. However, the lack of progress in this area could be attributed to the lack of tools to probe unbiasedly at the genome-wide level the coding and non-coding elements' contribution on a large scale for factors that control resistance to chemotherapeutics. Understanding the mechanisms of resistance to chemotherapeutics will enable precision medicine in the treatment of cancer patients. CRISPR Cas9a has emerged as a functional genomics tool to study at the genome level the factors that control cancer resistance to drugs. Recently, we used genome-wide CRISPR-Cas9a screen to identify genes responsible for glioblastoma susceptibility to etoposide. We extended our inquiry to understanding genes that control glioblastoma response to temozolomide using the genome-scale CRISPR. This study shows that the unbiased genome-wide loss of function approach can be applied to discover genes that influence tumor resistance to chemotherapeutics and contribute to chemoresistance in glioblastoma.